Pengaruh Etilen Tomat (S. lycopersicum) terhadap Pematangan Buah Pisang Muli (M. Acuminata L. ) - Dea Fitri Afifah; Muhammad Naufal Daffa; Oryza Aprilia Devina; Siti Nur Shifa Sholihat; Taufik Rahman; Tri Suwandi (AGROMAKNA: Jurnal Pertanian dan Peternakan, 2026)
Ethylene gas is produced by horticultural products, namely climacteric fruit that can continue to undergo a ripening process even though it has been harvested from the tree. Ethylene produced by plants has a dual role in controlling growth as well as aging in plants. The fruit ripening process is suppressed by controlling ethylene production and plant sensitivity to ethylene. This study aimed to identify the effect of ethylene produced by tomatoes on weight loss and color change in Muli bananas after harvesting. The method used was by grouping two treatments, namely treatment A as control (bananas), and treatment B (bananas together with tomatoes) and placed in a container such as cardboard, stored at room temperature for 5 days. The results showed that the ethylene contained in tomatoes accelerated the ripening of muli bananas in the form of weight loss and even color changes in the muli banana peels compared to storage that did not use tomatoes.